Dynamics of stigmatization and discrimination on intention to disclose among PLWHA: A qualitative assessment (2012)
UNAIDS (2010) estimated that about 33 million adults are HIV positive, while more than 15 million children worldwide are orphaned by the HIV scourge. Some psychosocial factors contributing to the challenge of combating the HIV phenomenon include stigmatization and discrimination. Research findings have shown that HIV positive individuals are reluctant to disclose their status and access medical care because of the fear of stigmatization and discrimination. Adopting a qualitative approach, this study investigated the dynamics of stigmatization and discrimination on intention to disclose HIV status. In-depth interviews (lDIs) and focus group discussions were conducted. A thematic analysis indicated that there exist stigmatization and discrimination at individual and societal levels against people living with HIV and AIDS, these were as a result of the way HIV and AIDS were represented at the initial stage as a condition that defies any solution. Media representations over time presented HIV and AIDS as dreaded monster that cannot be tamed. Cultural factors also fuel stigmatization and discrimination. Another factor enhancing stigmatization and discrimination is lack of effective policy framework to protect PLWHA from stigmatization and discrimination. It is concluded that stigmatization and discrimination are still prevalent and to combat them there should be effective legislations and enforced policies to protect PLWHA and community-based approach to disseminate appropriate HIV/AIDS knowledge. Also, media adverts should exclude subtle stigmatization representations while cognitive restructuring and attitudinal change programmes should be aggressively embarked upon for the larger society to adopt the right attitude toward PLWHA.